V0.03 - Valuation of the redesigned lateral bracing system and relevant work - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding V0.03 - valuation of the redesigned lateral bracing system and relevant work of Brac University new campus development project .